2003
DOI: 10.1002/cncr.11473
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the ability of serial measurements of serum chromogranin A and gastrin to detect changes in tumor burden in patients with gastrinomas

Abstract: This article reports densities and viscosities up to 60 MPa and from 303.15 to 353.15 K on two binary mixtures of CO2 and lubricant pentaerythritol tetra‐2‐ethylhexanoate with 7.8% and 14.4% mass fraction of lubricant. Because CO2 and the lubricant are not in the same phase at atmospheric pressure and room temperature, a specially‐designed vibrating‐wire apparatus has been used. The experimental data, together with our previous data for six mixtures of CO2 and three polyolesters, have been used to test the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…2, no positive correlation is seen between ghrelin and chromogranin A, a biochemical marker for NETs, in patients with hepatic metastases. In previous studies, CgA has been shown to have low sensitivity and specificity for detecting tumor increases and stabilization (Abou-Saif et al 2003). It therefore is not surprising to see poor correlation here.…”
Section: Discussionmentioning
confidence: 60%
“…2, no positive correlation is seen between ghrelin and chromogranin A, a biochemical marker for NETs, in patients with hepatic metastases. In previous studies, CgA has been shown to have low sensitivity and specificity for detecting tumor increases and stabilization (Abou-Saif et al 2003). It therefore is not surprising to see poor correlation here.…”
Section: Discussionmentioning
confidence: 60%
“…It might well be that the 3-mo follow-up after PRRT was too brief an interval for detecting true responses by tumor markers, especially given that there may have been a paradoxic elevation (i.e., due to treatment-related secretion) in the early posttreatment reassessment. Basically, the plasma chromogranin A level had low specificity for predicting changes in tumor size among human gastrinoma patients and varied considerably from day to day (32). In several previous clinical studies, chromogranin A levels failed to correlate with the NET mass (33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, several recent therapeutic trials on NETs demonstrated its prognostic value , Yao et al 2011b. Several authors reported correlations between CgA variations during treatment and RECIST-assessed tumor evolution (Bajetta et al 1999, Seregni et al 2001, Abou-Saif et al 2003, Kouvaraki et al 2004, Nehar et al 2004, Jensen et al 2007, Yao et al 2011b. Early CgA response (R30% decrease at week 4) was correlated with improved median PFS, median OS, and tumor responses, compared with patients without early CgA responses (Table 3; Yao et al 2010a, 2011b.…”
Section: Biological Markers Tumor Progression and Therapeutic Respomentioning
confidence: 96%